The implications of the growth of the extreme right and populism in Western countries on the victims of Arab forced migration and their integration into the host societies - Benayache, Samir (Journal of Human Sciences, 2020)
The number of migrants forcibly increased to Western countries, due to wars, armed conflicts and instability, widespread injustice, oppression, lack of freedoms, harsh climate, and the failure of the European Union to face the largest displacement crisis in the world since World War II, although this phenomenon will revive their economies As for the extreme right and populist tide, he exploited the phenomenon for his election campaigns. In the future, resolving the crises causing this migration will contribute to reducing the number of migrants, but there are problems that remain as the integration of migrants into the destination countries, where the right and populist movements have complicated it because of the difficulty of voluntary repatriation because the wars are still raging, and the resettlement in third countries, From its cases up to the Arab trying to get rid of migrants although their return is unsafe, the international community and host communities, and even the migrants themselves are required to respect human rights, and in the positive change in the outlook towards Muslim and Arab immigrants, this requires great efforts and a long time, but will serve the parties concerned by this phenomenon.